2016
DOI: 10.1007/s13361-016-1363-7
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding and Folding of the Three-Helix Bundle Protein KIX in the Absence of Solvent

Abstract: Electron capture dissociation was used to probe the structure, unfolding, and folding of KIX ions in the gas phase. At energies for vibrational activation that were sufficiently high to cause loss of small molecules such as NH3 and H2O by breaking of covalent bonds in about 5% of the KIX (M + nH)n+ ions with n = 7–9, only partial unfolding was observed, consistent with our previous hypothesis that salt bridges play an important role in stabilizing the native solution fold after transfer into the gas phase. Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 83 publications
(61 reference statements)
3
26
0
Order By: Relevance
“…More broadly, through detailed comparisons of CIU fingerprints, quantified using RMSD values, our CIU experiments reveal that the differences in the observed CIU features arise from the altered stabilities of the complexes imparted through peptide binding. We hypothesize that KIX unfolds in a linear α-helix 1-3 fashion in the gas-phase, which correlates well with previous ECD and CID experiments [22, 23]. Such a detailed understanding of the KIX CIU process, linking CIU features to specific regions of the KIX structure, may enable the development of improved PPI inhibitor binding assays.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…More broadly, through detailed comparisons of CIU fingerprints, quantified using RMSD values, our CIU experiments reveal that the differences in the observed CIU features arise from the altered stabilities of the complexes imparted through peptide binding. We hypothesize that KIX unfolds in a linear α-helix 1-3 fashion in the gas-phase, which correlates well with previous ECD and CID experiments [22, 23]. Such a detailed understanding of the KIX CIU process, linking CIU features to specific regions of the KIX structure, may enable the development of improved PPI inhibitor binding assays.…”
Section: Discussionsupporting
confidence: 86%
“…In particular, ECD of 7+ KIX ions revealed that the observed c and z • fragment ions mainly originated from the backbone near the protein termini, and not from the 3-helix bundle [22]. Further ECD and CID experiments found that the propensity for KIX folding is determined by the intramolecular distribution of charges on the protein surface, rather than its net charge, leading ultimately to produce the surprising stability of KIX in the gas-phase [23]. Together, these experiments showed the gas-phase stabilities of the KIX helices to be α3>α2>α1 [22], and in particular, for the 8+ charge state, α1 appears to be the least stable [23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first correlation of gaseous protein fragment ions to primary sequence in 1990 [9], MS/MS has been widely used to enable mass spectrometry-based analysis of peptides [10, 11, 12] and proteins [13, 14]. The process requires the measurement of the intact mass of the precursor, which is then isolated in the gas phase and activated to break its interresidue bonds.…”
Section: Introductionmentioning
confidence: 99%